DOI: 10.35537/10915/21965
|View full text |Cite
|
Sign up to set email alerts
|

Microvertebrados del Holoceno de sitios arqueológicos en el sur de Mendoza (República Argentina): aspectos tafonómicos y sus implicancias en la subsistencia humana

Abstract: Se estudiaron los ensambles de microvertebrados recuperados de nueve sitios arqueológicos del sur de Mendoza. A partir de un análisis tafonómico exhaustivo, se pudo concluir que las aves rapaces fueron los principales agentes acumuladores de los microvertebrados. El registro aislado de marcas de corte en una tibia de un roedor cávido, en un lapso de la secuencia de un sitio cordillerano (1380-770 14C años AP), indicó una débil señal de consumo antrópico sobre los microvertebrados. Por ende, no alcanza para def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 205 publications
(574 reference statements)
2
20
0
3
Order By: Relevance
“…It is important to mention that other non‐human taphonomic agents contributed to the faunal taxonomic compositions of these sites (especially those located in caves), creating more diverse assemblages. Numerous taphonomic studies in this region detected additional taxa related to activities of non‐human predators (Giardina, ; Fernández, ; Otaola, ; Otaola et al ., ). For this reason, in order to avoid an overestimation of faunal diversity, taxa with evidence of non‐human consumption were excluded from the taxonomic analyses.…”
Section: The Archaeofaunal Recordsupporting
confidence: 56%
See 1 more Smart Citation
“…It is important to mention that other non‐human taphonomic agents contributed to the faunal taxonomic compositions of these sites (especially those located in caves), creating more diverse assemblages. Numerous taphonomic studies in this region detected additional taxa related to activities of non‐human predators (Giardina, ; Fernández, ; Otaola, ; Otaola et al ., ). For this reason, in order to avoid an overestimation of faunal diversity, taxa with evidence of non‐human consumption were excluded from the taxonomic analyses.…”
Section: The Archaeofaunal Recordsupporting
confidence: 56%
“…However, recent research has demonstrated that not all the changes in the archaeofaunal assemblages can be associated with diet changes. On the contrary, many of the regional assemblage owed much to taphonomic process and natural resource distributions (Giardina, ; Otaola, 2012; Fernández, ; Otaola et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In Argentina, as in many other places, several archaeological sites are very rich in small rodent bones (Pardiñas, ; Fernández, ; and references therein). Different processes are responsible for the formation of these accumulations, and it is interesting to know what agents may have been involved in such formation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we can expect an overlapping of records accumulated by birds of prey that often make nests and roosts on rock shelters as different species of Tyto and Bubo do with those records generated by humans (Fernández, ). In this regard, the taphonomic differentiation of these agents is interesting for zooarchaeology, because it can provide relevant information about the predator/prey interaction and about the environmental conditions at the time of the deposition of the fossil aggregate (Stahl, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, during the last 5 years, research has shown a decrease in the importance of guanacos in human diet in relationship to other prey (Gil and Neme, ; Neme and Gil, ; Corbat et al ., ; Giardina, ). In this framework, different papers have called to attention the use of other taxa that provides a more realistic perspective about the variation in the zooarchaeological record in west central Argentina and surrounding areas (Giardina, ; Medina et al ., ; Fernández, ).…”
Section: Introductionmentioning
confidence: 97%